2014
DOI: 10.1007/s00259-014-2903-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of volumetric parameters of 18F-FDG PET in non-small-cell lung cancer: a meta-analysis

Abstract: Volumetric parameters from (18)F-FDG PET are significant prognostic factors for outcome in patients with NSCLC. Patients with a high MTV or TLG are at higher risk of adverse events and death. MTV and TLG were significant prognostic factors in patients with TNM stage I/II and stage III/IV NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(161 citation statements)
references
References 54 publications
6
151
1
3
Order By: Relevance
“…To overcome these limitations of SUV, MTV and TLG have been studied as prognostic factors for NSCLC (7,8,10,14,15 (10). Other studies have confirmed that TLG and MTV are better indices of patient survival than SUV max or mean SUV (7,8,10,14,15). Previous studies focused primarily on advanced-stage disease, and few studies have reported the role of volume-based parameters in early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations of SUV, MTV and TLG have been studied as prognostic factors for NSCLC (7,8,10,14,15 (10). Other studies have confirmed that TLG and MTV are better indices of patient survival than SUV max or mean SUV (7,8,10,14,15). Previous studies focused primarily on advanced-stage disease, and few studies have reported the role of volume-based parameters in early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…MTV indicates the volume of metabolically active tumor, and TLG is the product of mean SUV and MTV (6). Studies have shown that TLG is a better index of patient prognosis than SUV max in advanced NSCLC (7)(8)(9)(10)(11)(12). However, the prognostic role of volume-dependent parameters in stage IA NSCLC has not been reported.…”
mentioning
confidence: 99%
“…SUV maks değerinin hesaplanmasında lezyon çevresine çizilen ilgi alanı içinde yer alan ve maksimum aktiviteye sahip vokselden yapılan ölçüm dikkate alınır. Yakın zamanlı çalışmalar MTV ve TLG'nin hem primer tümörün hem de tüm vücuttaki toplam tümör yükünün yansıması olarak, ayrıca metabolik ve hacimsel bilgiyi bir araya getirmeleri nedeniyle SUV'ye göre prognozu öngörmede daha başarılı olduğunu işaret etmektedir (48,49,50,51,52). KHDAK'nin tüm evrelerinde yüksek MTV ve TLG yüksek advers olay riski ve düşük sağkalım ile ilişkilidir (48,51,52).…”
Section: Fdg Pet/bt Bulgularının Sayısal Analiziunclassified
“…Yakın zamanlı çalışmalar MTV ve TLG'nin hem primer tümörün hem de tüm vücuttaki toplam tümör yükünün yansıması olarak, ayrıca metabolik ve hacimsel bilgiyi bir araya getirmeleri nedeniyle SUV'ye göre prognozu öngörmede daha başarılı olduğunu işaret etmektedir (48,49,50,51,52). KHDAK'nin tüm evrelerinde yüksek MTV ve TLG yüksek advers olay riski ve düşük sağkalım ile ilişkilidir (48,51,52). KHDAK'sinde SUV maks MTV ve TLG'nin hasta prognozu ile ilişkisini değerlendirmeye yönelik çalışmaların derlendiği 36 makale ve 5807 hasta verisi içeren bir meta-analizde bu değerlerin cerrahi tedavi sonrası genel ve hastalıksız sağkalım bakımından öngörü değeri taşıdığı gösterilmiştir (53).…”
Section: Fdg Pet/bt Bulgularının Sayısal Analiziunclassified
“…PET/CT imaging provides anatomic and metabolic information, which is important for detection, localization, and characterization of the disease (2,3). Furthermore, quantitative indices in PET, such as standardized uptake value (SUV) (4,5), metabolic volume (6,7), and total lesion glycolysis (5-7), can be used to provide prognostic information and predict and monitor therapy response (4)(5)(6)(7).…”
mentioning
confidence: 99%